Combinación de estimulantes naturales en la germinación de semillas de cacao theobroma cacao l. en la granja Santa Inés - Heras Heras, Froilan Dionicio (2014)
On the Farm St. Ines was investigated on the properties of natural stimulants and water coconut water bamboo cane , to assist in the cocoa bean CCN- 51 to stimulate germination and growth process on schedule , taking into account the effect produced by such proportions The objectives were 1. Check the combined effect of natural stimulant in cacao seed germination, 2. Determine the growth of seedlings during the nursery phase, and 3. Establish production costs. The study area corresponds to Tropical dry forest (bms -T) with an average annual rainfall of 699 mm and an average annual temperature of 25 º C and a relative humidity of 84 %. The treatments investigated:T1pure coconut water; T2 Water bamboo cane;T3coconut water + bamboo water ( 25 +75 ); T4 Water Coconut + water of bamboo ( 50 +50 ); T5 Coconut water + water bamboo ( 75-25 ) and T6 Witness pure water. The assay was adjusted to a completely random design with six treatments and four replications, the variables studied were: plant height at 30, 60 and 90 days, number of functional leaves at 30, 60 and 90 days, stem diameter at 30, 60 and 90 days, root length at 90 days and root weight at 90 days. The seed without test they soak each stimulant combinations chosen for a period of 24 hours and proceeded to sow the seeds, one for each bag filled with substrate, prepared with 2 parts soil, 1 part sand, ½ part rice bran and ¼ of humus. The mixture was disinfected with formol 2 liter/m3 prepared substrate. The variable day’s cacao seed germination occurs without reading replicas, because it is a point estimate in the one with the average and standard deviation. In treatment T1 coconut water was the best result presented by his precocity and where plants from treated coconut water seeds emerged at 15 days, while the T6 (control) had the longest period to and seed germination was 19 days. The analysis of variance and means comparison tests on two variables , plant height at 30 days and root length high statistical significance was obtained in which the water is evidenced Coconut and bamboo cane , if processes influenced germination and growth of the stem and roots. Coconut water mixes with bamboo water had no positive effect , The Growth of roots cocoa plants evaluated in CCN -51 was slightly higher when using coconut water and 100% bamboo and leaves Issuing the plants remained in the nursery was similar across all treatments including the control.